2023
DOI: 10.1200/jco.22.02005
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and Behavioral Development of 9-Year-Old Children After Maternal Cancer During Pregnancy: A Prospective Multicenter Cohort Study

Abstract: Clinical trials frequently include multiple end points that mature at different times. The initial report, typically based on the primary end point, may be published when key planned co-primary or secondary analyses are not yet available. Clinical Trial Updates provide an opportunity to disseminate additional results from studies, published in JCO or elsewhere, for which the primary end point has already been reported. This multicenter cohort study reports on the long-term effects of prenatal exposure to mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…Previous studies have identified maternal mortality as a significant contributor to adverse neurocognitive and behavioral outcomes, 19–21 which is supported by previous findings from the INCIP cohort, showing subtle differences in both child language development and the child's need of supportive care after maternal death 9,21 . A subanalysis on chemotherapy‐exposed children with a median age of 9 years ( n = 151) also showed a trend of a need for supportive care after maternal bereavement, although this trend was not statistically significant and may be confounded by the high incidence of prematurity in this cohort 11 . Further research, especially in the long‐term, is thus required to elucidate the psychosocial and neurocognitive impact of maternal separation and maternal death on the child.…”
supporting
confidence: 88%
See 2 more Smart Citations
“…Previous studies have identified maternal mortality as a significant contributor to adverse neurocognitive and behavioral outcomes, 19–21 which is supported by previous findings from the INCIP cohort, showing subtle differences in both child language development and the child's need of supportive care after maternal death 9,21 . A subanalysis on chemotherapy‐exposed children with a median age of 9 years ( n = 151) also showed a trend of a need for supportive care after maternal bereavement, although this trend was not statistically significant and may be confounded by the high incidence of prematurity in this cohort 11 . Further research, especially in the long‐term, is thus required to elucidate the psychosocial and neurocognitive impact of maternal separation and maternal death on the child.…”
supporting
confidence: 88%
“…Regarding neurocognitive development, previous cohort studies on children prenatally exposed to chemotherapy, showed an overall reassuring development until the age of 6 years 8,9 . Furthermore, a report on the 9‐year‐old cohort, described a normal cognitive and behavioral development in late childhood when complex and executive functions are developing 11 . Also, a Danish nation‐wide cohort study examined the general mortality, somatic diagnoses, and psychiatric diagnoses observed in offspring exposed to maternal cancer during pregnancy.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is advised to start chemotherapy in the second or third trimester, that is, after week 14 of pregnancy 3–5. Previous studies have shown that chemotherapy during the second and/or third trimester of pregnancy does not affect the short-term cardiac and neurocognitive development of children, which is reassuring 2 6–9. Additionally, administering chemotherapy treatment to pregnant women has led to an increase in livebirths and decrease in iatrogenic preterm deliveries 1.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, although overall, children born from pregnancies complicated by maternal cancer perform within normal ranges for their age, chemotherapy-exposed children had a significantly lower verbal IQ at 6 years, and were 3 times more likely to wear glasses than non-exposed children. However, since there are many confounding factors in neurocognitive development of children, a direct link with prenatal chemotherapy exposure cannot be accurately established 1 6–8…”
Section: Introductionmentioning
confidence: 99%